Evaluasi Risiko Postur Kerja pada Aktivitas Lifting Menggunakan Push Pull Stick Berdasarkan Metode REBA - Frenky Satria; Rini Dharmastiti (Pusat riset dan Inovasi Nasional, 2026)
Lifting activities are an essential part of manual material handling across various industrial sectors and constitute a primary source of ergonomic risk exposure when performed with inappropriate work postures. The use of hands-off tools such as push-pull sticks is often implemented to maintain a safe distance between workers and loads and to reduce exposure to line-of-fire hazards. However, the implementation of work aids does not automatically ensure neutral work postures, as push-pull techniques, reach distances, and environmental conditions can still lead to awkward postures. This study aims to evaluate the work posture risk in lifting activities using a fiber-composite push-pull stick based on the Rapid Entire Body Assessment (REBA) method. The research was conducted as an observational analytic field study involving nine workers in tubular pushing and pulling activities. Work postures were documented through direct observation and visual recordings, then assessed using REBA to obtain risk scores, risk categories, and required corrective actions. The results indicate that work postures fall into the medium to high-risk categories, with trunk and shoulder components being the dominant contributors. These findings confirm the need for improvements in work methods, ergonomic training, and strengthening of lifting SOPs to optimize the safety and ergonomic benefits of work aids.